2006
DOI: 10.1002/eji.200636128
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of epitope recognition pattern in Ag85B and ESAT‐6 has a profound influence on vaccine‐induced protection against Mycobacterium tuberculosis

Abstract: To analyze the effect of vaccine delivery systems on antigen recognition and vaccine efficacy, we compared immune responses in mice immunized either with an adenovirus vector expressing a fusion of Ag85B and ESAT-6 or with the recombinant fusion protein in a liposomal adjuvant. Both vaccines induced high levels of antigen-specific IFN-c production. The adjuvanted protein vaccine induced primarily a CD4 T cell response directed to the epitope Ag85B 241-255 and gave efficient protection against subsequent Mycoba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 46 publications
6
56
0
2
Order By: Relevance
“…Transfer of early secretory antigenic target (ESAT)-6-specific memory Th1 cells to recipient mice before M. tuberculosis challenge showed that higher numbers of specific T cells confer better protection than lower numbers (35). However, numerous other animal and human studies have shown that the CD4 T-cell IFN-g response does not necessarily correlate with protection but may rather reflect bacterial load or degree of inflammation (25,(36)(37)(38)(39)(40). This is also consistent with our finding of the highest T-cell responses in TB-affected children.…”
Section: Discussionmentioning
confidence: 99%
“…Transfer of early secretory antigenic target (ESAT)-6-specific memory Th1 cells to recipient mice before M. tuberculosis challenge showed that higher numbers of specific T cells confer better protection than lower numbers (35). However, numerous other animal and human studies have shown that the CD4 T-cell IFN-g response does not necessarily correlate with protection but may rather reflect bacterial load or degree of inflammation (25,(36)(37)(38)(39)(40). This is also consistent with our finding of the highest T-cell responses in TB-affected children.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccine strategies affect the selection of epitopes that prime CD4 ϩ and CD8 ϩ T cells in ways that are not yet understood. We now recognize that the epitopes that stimulate T cells after vaccination can differ from the epitopes that stimulate T cells after M. tuberculosis infection (1,6). This scenario can result in antigen-specific T cells induced by vaccination that are unable to recognize infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…The most effective and practical way to elicit a CD8 + T cell response, whether experimentally or clinically, is to vaccinate with a viral vector or with plasmid DNA (for example see [107]). However, Skeiky et al have evaluated the vaccine 72F.…”
Section: Subunit Vaccinesmentioning
confidence: 99%
“…In another dramatic example of how the way a vaccine is delivered can alter which epitopes elicit immune T cells, Peter Andersen developed a fusion protein consisting of ESAT6 covalently linked to Ag85B as a subunit vaccine [107]. This vaccine elicits a CD4 + T cell dominated response to ESAT6 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] and Ag85B 241-255 , and induces protective immunity in C57BL/6 mice.…”
Section: Expert Commentarymentioning
confidence: 99%